2020
DOI: 10.7554/elife.56920
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the intrinsic properties of striatal cholinergic interneurons after dopamine lesion and chronic L-DOPA

Abstract: Changes in striatal cholinergic interneuron (ChI) activity are thought to contribute to Parkinson's disease pathophysiology and dyskinesia from chronic L-3,4-dihydroxyphenylalanine (L-DOPA) treatment, but the physiological basis of these changes is unknown. We find that dopamine lesion decreases the spontaneous firing rate of ChIs, whereas chronic treatment with L-DOPA of lesioned mice increases baseline ChI firing rates to levels beyond normal activity. The effect of dopamine loss on ChIs was due to decreased… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 72 publications
1
37
0
Order By: Relevance
“…In addition, chronic L -DOPA administration enhanced baseline and DA-induced firing rates compared with chronic saline treatment in striatal ChIs of Pitx3 –/– mice ( Ding et al, 2011 ). The follow-up study by the same group showed that both hyperpolarization–activation cyclic nucleotide-gated and small conductance calcium-activated potassium (SK) channels mediate the change of ChI firing rates in response to chronic L -DOPA treatment ( Choi et al, 2020 ).…”
Section: Theoretic Models Of Bg In Lidmentioning
confidence: 99%
“…In addition, chronic L -DOPA administration enhanced baseline and DA-induced firing rates compared with chronic saline treatment in striatal ChIs of Pitx3 –/– mice ( Ding et al, 2011 ). The follow-up study by the same group showed that both hyperpolarization–activation cyclic nucleotide-gated and small conductance calcium-activated potassium (SK) channels mediate the change of ChI firing rates in response to chronic L -DOPA treatment ( Choi et al, 2020 ).…”
Section: Theoretic Models Of Bg In Lidmentioning
confidence: 99%
“…17 However, ex vivo studies in rodent models of PD have found no or modest changes of intrinsic tonic activity in SCINs 14,18,19 that can be partially reverted by L-dopa treatment. 20 Because PD becomes seriously debilitating when motor fluctuations and LID emerge, detailed studies in the off-state of L-dopa medication are needed. If chronic L-dopa exposure further disrupts SCIN activity in this condition, then SCIN potential as a therapeutic target to treat PD and LID increases.…”
mentioning
confidence: 99%
“…In vivo studies found that striatal tonically active neurons (putative SCINs) exhibit enhanced spontaneous oscillatory activity in parkinsonian monkeys that persists during the off‐state of l ‐dopa medication 17 . However, ex vivo studies in rodent models of PD have found no or modest changes of intrinsic tonic activity in SCINs 14,18,19 that can be partially reverted by l ‐dopa treatment 20 . Because PD becomes seriously debilitating when motor fluctuations and LID emerge, detailed studies in the off‐state of l ‐dopa medication are needed.…”
mentioning
confidence: 99%
“…The universality and nonselective cation permeability make HCN channels indispensable for cell excitability. Not only in pyramidal neurons, interneurons excitability homeostasis disorder also can trigger psychosis[51, 52]. Simultaneously, HCN channels engage on intracellular cascade reaction, like work as a downstream of some neurotransmitter receptors such as alpha-2 (α 2 ) adrenergic receptor, and the location of HCN channels in post-synapse membrane also facilitate they involve in synaptic signaling[28].…”
Section: Discussionmentioning
confidence: 99%